Current role of prostate-specific membrane antigen-based imaging and radioligand therapy in castration-resistant prostate cancer - Chen, Jiaxian; Qi, Lin; Tang, Yongxiang; Tang, Guyu; Gan, Yu; Cai, Yi (Frontiers in Cell and Developmental Biology, 2022)
.Castration-resistant prostate cancer (CRPC) is a therapy-resistant and lethal form of prostate cancer (PCa) as well as a therapeutic challenge. Prostate-specific membrane antigen (PSMA) has been proved as a promising molecular target for optimizing the theranostics for CRPC patients. When combining with PSMA radiotracers, novel molecular imaging techniques such as positron-emission tomography (PET) can provide more accurate and expedient identification of metastases as compared to conventional imaging techniques. Based on the PSMA-based PET scans, the accurate visualization of local and disseminative lesions may help in metastasis‑directed therapy (MDT). Moreover, the combination of 68Ga-labeled PSMA-based PET imaging and radiotherapy using the PSMA radioligand therapy (RLT) becomes a novel treatment option for CRPC patients. The existing studies have demonstrated this therapeutic strategy as an effective and well-tolerated therapy among CRPC patients. PSMA-based PET imaging can accurately detect CRPC lesions and describe their molecular features with quantitative parameters, which can be used to select the best choice of treatments, monitor the response, and predict the outcome of RLT. This review discussed the current and potential role of PSMA‐based imaging and RLT in the diagnosis, treatment and prediction of prognosis of CRPC.